Plant Growth-Promoting Bacteria: Biological Tools for the Mitigation of Salinity Stress in Plants - Kumar, Akhilesh; Singh, Saurabh; Gaurav, Anand Kumar; Srivastava, Sudhakar; Verma, Jay Prakash (Frontiers in Microbiology, 2020)
Salinity stress is one of the major abiotic stresses threatening sustainable crop production worldwide. The extent of salinity affected area is expected to cover about 50% of total agricultural land by 2050. Salinity stress produces various detrimental effects on plants’ physiological, biochemical, molecular features and reduces productivity. The poor plant growth under salinity stress is due to reduced nutrient mobilization, hormonal imbalance, and formation of reactive oxygen species (ROS), ionic toxicity, and osmotic stress. Additionally, salinity also modules physicochemical properties and reduces microbial diversity of soil and thus decreases soil health. On the other hand, the demand of crop production is expected to increase in coming decades owing to increasing global population. The conventional agricultural practices and improved salt-tolerant crop varieties would not be sufficient in achieving the desired yields in the near future. Plant harbour diverse microbes in their rhizosphere, which have the potential to cope up with the salinity stress. These salinity tolerant plant growth-promoting bacteria (PGPB) assist the plants to withstand saline conditions. These plants associated microbes produce different compounds such as 1-aminocyclopropane-1-carboxylate (ACC) deaminase, indole-3-acetic acid (IAA), antioxidants, extracellular polymeric substance (EPS), and volatile organic compounds (VOC). Additionally, the naturally associated microbiome of plants has the potential to protect host through stress avoidance, tolerance, and resistance strategies. The recent developments in microbiome research have shown ways for novel microbe-assisted technologies for enhancing plants’ salt tolerance and gain higher crop production under saline conditions. This focused review article presents the global scenario of salinity stress and discussed the research highlights about PGPB and microbiome as a biological tool for mitigation of salinity stress in plants.